Monitoring errors in a blood bank immunohematology laboratory: Implementing strategies for safe blood transfusion - Sudipta Sekhar Das; Ritam Chakrabarty; R U Zaman (Global Journal of Transfusion Medicine, 2017)
Background: Errors occurring at patient bedside during specimen collection are the most common causes of adverse outcomes. We planned this prospective study to estimate the incidence and nature of transfusion errors, identify the source, site of occurrence, and assess the underlying problems in the system with the aim to prevent the potentially fatal human error. Materials and Methods: The study was performed over a period of 5 years at a hospital based blood transfusion service where all errors and discrepancies both in the recipient and donor samples were reported into an 'incident and error reporting register' and then analyzed. Results: While a total of 72,381 patient samples were received for pretransfusion testing, 43,762 samples were from blood donors for ABO and Rh grouping. A total of 79782 blood components were issued to patients during the study. Out of 229 errors in the blood transfusion chain, 164 (0.22% of total requisitions and 0.21% of total component issued) were reported in patient pretransfusion samples, and 65 errors (0.15%) were reported in donor samples. Majority of the errors were clerical in nature and related to human errors. Of the 164 errors in pretransfusion testing samples, 107 (65.2) were observed in night shift. The overall error frequency per 1000 requisitions was 2.26. Conclusion: Near miss event reporting can prevent potential transfusion associated mortality and morbidity caused by simple human ignorance. A good error reporting not only helps in accurate collection and analysis of data but also makes recommendations that improve transfusion safety.